Diagnostic findings in a lame-free dog with complete rupture of the biceps brachii tendon - Wiemer, P.; van Ryssen, B.; Gielen, I.; Taeymans, O.; van Bree, H. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
A case of a complete rupture of the biceps brachii tendon in a lame-free three-year-old Labrador Retriever is described. The dog had a history of chronic lameness following a trauma, but had become lame-free shortly before presentation. Clinical examination, biceps tendon test and shoulder instability tests under general anaesthesia were inconspicuous for shoulder instability. Routine radiographs, arthrography and ultrasound were suspicious for bicipital tendopathy. The definite diagnosis of a complete rupture of the biceps brachii tendon was made upon arthroscopic inspection of the glenohumeral joint.
Keywords: Biceps brachii; tendon; rupture; diagnostic findings; dog